2003
DOI: 10.1002/adma.200306042
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Magnetic Iron Sulfide Nanowires

Abstract: equipped with a 150 lines mm ±1 grating and registered by an optical multichannel analyzer (OMA, Hamamatsu Photonics, PMA50 Synthesis and Characterization of Magnetic Iron Sulfide NanowiresBy Manashi Nath, Amitava Choudhury, Asish Kundu, and C. N. R. Rao* A variety of inorganic nanowires have been synthesized in the last three to four years.[1] Among these, magnetic nanowires are of interest because of their potential applications in magnetic recording and other areas. Nanowires and nanorods of magnetic metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
70
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 29 publications
1
70
1
Order By: Relevance
“…Many works have shown that EN solvent can function as molecular template directing the growth of nanomaterials of transition metal sulfides by chelating with metal ions including Zn 2+ , Cd 2+ , Ni 2+ and so on [11][12][13]. There are many phases of iron sulfides and some are important magnetic and optoelectrical materials with potentials in storage and solar cell [14,15]. Some high temperature physical or chemical vapor routes to FeS 2 films or nanostructures [15][16][17], low temperature solvothermal technique has been employed to synthesize iron sulfide nanomaterials including Fe 7 S 8 and Fe 1Àx S nanowires [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many works have shown that EN solvent can function as molecular template directing the growth of nanomaterials of transition metal sulfides by chelating with metal ions including Zn 2+ , Cd 2+ , Ni 2+ and so on [11][12][13]. There are many phases of iron sulfides and some are important magnetic and optoelectrical materials with potentials in storage and solar cell [14,15]. Some high temperature physical or chemical vapor routes to FeS 2 films or nanostructures [15][16][17], low temperature solvothermal technique has been employed to synthesize iron sulfide nanomaterials including Fe 7 S 8 and Fe 1Àx S nanowires [14].…”
Section: Introductionmentioning
confidence: 99%
“…There are many phases of iron sulfides and some are important magnetic and optoelectrical materials with potentials in storage and solar cell [14,15]. Some high temperature physical or chemical vapor routes to FeS 2 films or nanostructures [15][16][17], low temperature solvothermal technique has been employed to synthesize iron sulfide nanomaterials including Fe 7 S 8 and Fe 1Àx S nanowires [14].…”
Section: Introductionmentioning
confidence: 99%
“…ethylenediamine) nanowires, which were obtained by a solvothermal method in ethylenediamine media. [25] Herein is reported the selective synthesis of cubic Fe 3 S 4 , orthorhombic FeS 2 , and cubic FeS 2 by using an alternative sulfur precursor and with the aid of a magnetic field under hydrothermal conditions. The successful access to metastable phase greigite is consistent with the fact that greigite is stable over periods of several million years in nature and also exists as a sediment.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years low-dimensional nano and micromaterials in the tube, rod, wire and belt form have been the focus of extensive research owing to their novel optical, electrical, magnetic and catalytic properties, which are different from those of bulk materials [1][2][3][4][5][6]. Moreover, these materials have shown interesting applications in the emerging area of optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%